Present and Future of the Energy Dialogue Russia – EU (Development of Energy Dialogue of Russia and EU in 2012) - K E. Petrov (Vestnik MGIMO-Universiteta)
This paper describes the development of energy dialogue between Russia and the EU in 2012. It also focuses on the analysis of the contradictions that exist between the sides. The urgency of the topic is stressed, in particular, by the fact that, according to the EU's view, gas imports into the EU will continue to grow up to 2030 year, and the European countries will have to purchase additional volumes of Russian gas. This means that the window of dialogue opportunities will expand continuously, but dialogue is severely hampered in this particular period of time. Even the subject of the dialogue is understood differently. Russia wants to, first of all, discuss measures to establish a joint system of reliable gas supply to Europe. The EU would like to concentrate on the problems of infrastructure and energy efficiency. This paper presents an overview of the factors influencing the dialogue between Russia and the EU. Among which are: the reduction of gas production in the EU, the market power of Gazprom, the expansion of shale gas, increased financial liquidity of gas, the fight for market transparency. The last factor, represented chiefly in the antitrust proceedings around «Gazprom» and the first results of the entry into force of the rules of the third energy package, pulled in more detail. In conclusion emphasizes that the removal of contradictions gets serious damage due to the fact that the European Commission is negotiating on behalf of the common customer of energy, and the Russian Federation – on behalf of the corporation.